Analisis Pengaruh Kualitas Pelayanan Harga Dan Lokasi Terhadap Kepuasan Konsumen Pada Bengkel Omega Kalabahi Kabupaten Alor (Studi Kasus Pada Bengkel Omega Kalabahi Kabupaten Alor) - Dollu, Agabus Yermias; Maruli, Elia; Awang, Mesak Y.; Anigomang, Ferdinand Romelus (Jurnal Ilmiah Wahana Pendidikan, 2023)
Consumer satisfaction is a person's level of satisfaction after comparing the perceived performance or results compared to the desired expectations and in this study aims to determine the effect of service quality, price and location. This type of research is quantitative research with data collection techniques, namely observation, interviews, and documentation studies. This study uses population primary data and the sample is consumers who use services or buy products/goods at the Omega Kalabahi Workshop, Alor Regency, totaling 30 consumers. And the sampling technique in this study is the Accidental Sampling (accidental) method. The statistical method used in this study is multiple linear regression. The results of this study indicate that: (1). Partially the service quality variable has a significant value of 0.000 or 0% where this value is smaller than the alpha value of 0.05 or 5% so that the results of this study accept H1 which states that service quality partially has a positive effect on customer satisfaction at the Omega Kalabahi Workshop Alor District. (2). Partially the price variable has a significant value of 0.019 or 0.19% where this value is smaller than the alpha value of 0.05 or 5% so that the results of this study accept H2 which states that price partially has a positive effect on customer satisfaction at the Omega Kalabahi Workshop Alor District. (3). Partially the location variable has a significant value of 0.028 or 0.28% where this value is smaller than the alpha value of 0.05 or 5% so that the results of this study accept H3 which states that location partially has a positive effect on customer satisfaction at the Omega Kalabahi Workshop Alor District. (4). Simultaneously the price and location service quality variables have a significant value of 0.000 or 0% where this value is smaller than the alpha value, namely H4 which states that the price and location service quality variables simultaneously have a positive effect on customer satisfaction at the Omega Kalabahi Workshop, Alor Regency. (5). The magnitude of the influence of the price and location service quality variables is 93.9%, this study simultaneously accepts H5.